The effects of myo-inositol and probiotic supplementation in a high-fat-fed preclinical model of glucose intolerance in pregnancy. Issue 5 (27th November 2019) - Plows, J. F.; Ramos Nieves, J. M.; Budin, F.; Mace, K.; Reynolds, C. M.; Vickers, M. H.; Silva-Zolezzi, I.; Baker, P. N.; Stanley, J. L.
Abstract: Glucose intolerance during pregnancy – a major driver of gestational diabetes mellitus (GDM) – has significant short- and long-term health consequences for both the mother and child. As GDM prevalence continues to escalate, there is growing need for preventative strategies. There is limited but suggestive evidence that myo-inositol (MI) and probiotics (PB) could improve glucose tolerance during pregnancy. The present study tested the hypothesis that MI and/or PB supplementation would reduce the risk of glucose intolerance during pregnancy. Female C57BL/6 mice were randomised to receive either no treatment, MI, PB ( Lactobacillus rhamnosus and Bifidobacterium lactis ) or both (MIPB) for 5 weeks. They were then provided with a high-fat diet for 1 week before mating commenced and throughout mating/gestation, while remaining on their respective treatments. An oral glucose tolerance test occurred at gestational day (GD) 16·5 and tissue collection at GD 18·5. Neither MI nor PB, separately or combined, improved glucose tolerance. However, MI and PB both independently increased adipose tissue expression of Ir, Irs1, Akt2 and Pck1, and PB also increased Pparγ . MI was associated with reduced gestational weight gain, whilst PB was associated with increased maternal fasting glucose, total cholesterol and pancreas weight. These results suggest that MI and PB may improve insulin intracellular signalling in adipose tissue but this did not translate to meaningful differences in glucose tolerance. The absence of fasting hyperglycaemia or insulin resistance suggests this is a very mild model of GDM, which may have affected our ability to assess the impact of these nutrients.